Comparison of the results for calculation of vortex currents after sudden expansion of the pipe with different diameters - Kholboev, Bakhodir Murodovich; Navruzov, Dilshod Primkulovich; Asrakulova, Dono Sunnatullaevna; Engalicheva, Nelia Rustamovna; Turemuratova, Ariukhan Abatbayevna (Zielona Góra: Uniwersytet Zielonogórski)
In this work, a numerical study of a sharply expanding highly swirling flow is carried out using v2-f models based on the Comsol Multiphysics 5.6 software package and a two-fluid turbulence model. The results obtained are compared with known experimental data with different pipe diameters. The purpose of this work is to test the ability of models to describe anisotropic turbulence. It is shown that the two-fluid model is more suitable for studying such flows.
Keywords: two-fluid turbulence model; sudden expansion; velocity fluctuation; intensity of fluctuations; gas resistance; quasi-periodic regime